Further delineation of Nevo syndrome. Issue 5 (May 1997) - al-Gazali, L I; Bakalinova, D; Varady, E; Scorer, J; Nork, M
Abstract : Nevo syndrome is an autosomal recessive syndrome characterised by prenatal overgrowth, joint laxity, kyphosis, wrist drop, spindle shaped fingers, and volar oedema. Four children from two families have been reported previously. We report two further children from two unrelated Arab families from two different tribes. Both presented at birth with hypotonia, joint laxity, kyphosis, wrist drop, spindle shaped fingers, and volar oedema. Both have delayed motor development at the ages of 2 years 10 months and 3 months respectively. Cognitive development is normal in one, and the other case appears to be developing normally at 3 months of age. One has, in addition, a wide spinal canal on MRI of the spine indicating some degree of dural ectasia. This report brings the total number of children reported with this syndrome to six from four families; three of these families are Arab. This indicates that the gene for this syndrome is probably commoner in Arabs than in other populations.